Indigenous Knowledge, Ecology, and Evolutionary Biology - E. N. Anderson (Ethnobiology Letters, 2011)
Review of Indigenous Knowledge, Ecology, and Evolutionary Biology. Raymond Pierotti. 2011. Routledge (Taylor & Francis Group), New York.  Pp. Xv + 264, Bibliography, index.  ISBN13: 978-0-415-87924-8 (hbk), 978-0-203-84711-4 (ebk).